Understanding the physical and chemical properties of keratin films - Chia, Sheryl CaiYing. (2013)
Hair is seen as a waste material to be discarded after a haircut. However this waste material can be reused as a biomaterial for greater applications such as wound dressing applications or skin reconstruction. Hair is made up predominantly of keratin, which is a biopolymer that is biocompatible and biodegradable. It is also found as keratinocytes on skin forming a protective layer to inhibit passage of environmental contaminants or pathogens. Hence, keratin is a promising biopolymer to be explored.